Al-Ism fī Kitāb Al-Naḥw al-ʿAṣrī li-Sulaymān Fayyāḍ - Alif Cahya Setiyadi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
Numerous books on Arabic grammar have been produced, each employing different methodologies and approaches to the study of syntax. Among these works, Al-Naḥw al-ʿAṣrī by Sulaymān Fayyāḍ is regarded as one of the most important references for simplifying the rules of Arabic grammar. The book adopts a distinctive methodology and instructional approach in teaching Arabic syntax. One of Sulaymān Fayyāḍ's grammatical views is his definition of the noun (ism) as every word that denotes an entity perceived either through the senses or by the intellect, without reference to time. He further argues that lexical items fall into three grammatical case categories: the nominative, accusative, and genitive. In addition, he treats the dependent elements (al-tawābiʿ), which may occur in all three grammatical cases, as an independent topic separate from the discussion of nouns classified according to these case endings. One of the distinguishing features of this book is its clear presentation of grammatical rules through numerous examples organized in tabular form, making the material easier to understand and apply.